Effects of Habitat Change on the Web Characteristics and Fitness of the Giant Wood Spider (Nephila pilipes) in Sri Lanka - Wijerathna, Tharaka; Tharanga, Dilini; Perera, Inoka C.; Wijesinghe, M.R. (My University, 2019)
Loss and fragmentation of rainforests have led to serious implications on the survival of many species, ofen leading to population decline, or sometimes local extinction. Spiders are key inhabitants of rainforest ecosystems and, in ever changing tropical landscapes, their response to habitat change would be an important factor in deciding their fate. Web building spiders rely solely on their webs to entrap prey. Architectural and other properties of the web would therefore be expected to have a strong infuence on the efciency of prey capture. Limited evidence from captive studies has demonstrated that spiders alter web properties in response to changes in environmental conditions [1–5]. Some reported facts of interest are as follows: web size is infuenced by the intensity of hunger such that starved spiders build larger webs than satiated spiders [6] microclimatic conditions around the web infuence mesh size [5] properties of the silk thread vary with changes in prey availability [7–11]. Accordingly, we would expect habitat change, from forest to nonforest, to bring about changes in web properties of the rainforest spiders.
Keywords: Effects of Habitat Change on the Web Characteristics and Fitness of the Giant Wood Spider (Nephila pilipes) in Sri Lanka